Penerapan Nilai-Nilai Pancasila dalam Kehidupan Sehari-Hari oleh Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya - Agustina, Intan Aulia; Agustian Susanto, Morio Cavin; Al Haq, Azza Kamila; Ika Puspita, Ari Metalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Industrial Revolution 4.0, which is characterized by rapid technological development and social change, the implementation of the noble values of Pancasila is increasingly relevant to form a tolerant, ethical, and nationalist young generation. This study aims to observe the implementation of Pancasila values by students of the Faculty of Economics and Business (FEB), Surabaya State University. The observation results show that students actively internalize the values of Pancasila through various social, religious, and academic activities. However, some challenges such as courage in expressing opinions and equitable internet access still need to be overcome to support the implementation of Pancasila more optimally. In conclusion, students show a strong commitment to the values of Pancasila, but support for character strengthening programs by educational institutions and the government is needed. Improving digital facilities, collective awareness, and social skills development programs are strategic steps to ensure that Pancasila values continue to guide the lives of the younger generation.